STRATEGI PENINGKATAN PRESTASI BELAJAR PASING BOLA VOLI PADA SISWA KELAS VI SDI ORINGBELE MELALUI MEDIA BOLA TIRUAN DARI BAHAN LOKAL - Paulus, Paron Bolen (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
In providing the facilities and media, the researchers took the initiative to invite students to make artificial volleyball modifications so that they could be used as a medium in learning volleyball games. The purpose of this study was to determine the extent to which volleyball modified media made from dried banana leaves or rounded old newspapers as big as volleyball and then wrapped with dried banana bark and then woven with banana ropes, in class VI SDI Oringbele. This type of research is classroom action research conducted in 2 cycles. The subjects of this study were 30th grade students of SDI Oringbele, amounting to 30 people. To collect data, researchers observed the activities of students in passing volleyball, questionnaires. The results of student activities stated an increase of 90%. referring to the Student Activity Indicator, the amount of activity is 85% including the Good criteria. The results of the observation of the first cycle reached 90%. The results of reflection on learning completeness for the prefix aspect reached 90% of sons and daughters reaching 100%.